Non-performing loan performance from banking industry perspective of Bangladesh: a study on Sonali Bank’s non-performing loan - Haque, Jannat-Ara (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.